Expanding Host Range: First Record of Eustrongylides excisus in Padogobius bonelli (Gobiidae) from the Po River (Northwest Italy) - Alessandra Maganza; Camilla Mossotto; Alice Gabetti; Rodolphe Elie Gozlan; Marine Combe; Giuseppe Esposito; Fabio Bondavalli; Marco Bertoli; Elisabetta Pizzul; Paolo Pastorino; Marino Prearo (Fishes, 2025)
Fish-borne parasites encompass diverse taxonomic groups, including nematodes of the genus Eustrongylides (family Dioctophymatidae), which infect fish, fish-eating birds, and, occasionally, humans. Eustrongylides spp. are globally distributed, with E. ignotus and E. tubifex prevalent in North America, while E. excisus is more frequent in Europe and the Middle East. This study investigates the presence of E. excisus in a fish community of the Po River (Turin, northwest Italy). Among 170 fish sampled from three sites along the Po River, only two Padogobius bonelli individuals from the Murazzi site were found to be infected, each hosting a single larva within the abdominal cavity. Molecular analysis (ITS rDNA sequencing) confirmed the parasite as E. excisus, showing 100% identity with known sequences. Although prevalence in this study was low (1.18%), the findings significantly expand the known host range of E. excisus, previously reported only in other gobiid species in Eastern Europe. The parasite is widely distributed in Italy, especially in commercial fish from large lakes, and its spread is facilitated by oligochaete intermediate hosts and piscivorous birds like cormorants. Given the benthic habits and diet of P. bonelli, increased monitoring is needed to better understand the parasite’s transmission dynamics and the potential risks to native biodiversity and human health.